Valuing the acute subjective experience - Cheung, K; Earp, BD; Yaden, DB (Johns Hopkins University Press, 2024)
Psychedelics, including psilocybin, and other consciousness-altering compounds such as 3,4-methylenedioxymethamphetamine (MDMA), currently are being scientifically investigated for their potential therapeutic uses, with a primary focus on measurable outcomes: for example, alleviation of symptoms or increases in self-reported well-being. Accordingly, much recent discussion about the possible value of these substances has turned on estimates of the magnitude and duration of persisting positive effects in comparison to harms. However, many have described the value of a psychedelic experience with little or no reference to such therapeutic benefits, instead seeming to find the experience valuable in its own right. How can we make sense of such testimony? Could a psychedelic experience be valuable even if there were no persisting beneficial effects? If so, how? Using the concept of psychological richness, combined with insights from the philosophy of aesthetics and the enhancement literature, this essay explores potential sources of value in the acute subjective experience, apart from the value derived from persisting beneficial effects.